RUSSIA-ZAMBIA: STAGES AND HORIZONS OF COOPERATION - PROKOPENKO Lyubov Yaroslavovna (Ученые записки Института Африки Российской академии наук)
The article shows the dynamics of the development of the 55-year-long cooperation between the USSR/Russia and Zambia, as well as the characteristics of the first stage of the cooperation between our countries during the period when the United Party of National Independence (UNIP) led by Kenneth Kaunda was in power, and later in the 1990s when contacts were limited.